Metabólitos secundários em Vernonia tweedieana Baker - Zanon, Ricardo Basso (2006)
The species Vernonia tweedieana Baker is an herbaceous plant widely distributed in the plains of Paraguai, Argentina and south of Brazil and popularly known as assa-peixe . This plant is used in traditional medicine as an expectorant medicament. So far, this plant was not studied on the phytochemical and biological point of view. This work is a contribution to the phytochemical study of the Asteraceae. The leaves of V. tweedieana Baker were collected in march of 2004, in Ijuí Rio Grande do Sul, Brazil, and identified by Dr. Geraldo C. Coelho (UNIJUÍ). The respective voucher specimen was deposited in the herbarium of the Federal University of Santa Maria (UFSM)-RS (code SMDB 9536). The leaves (1.900 g) were dried in an air circulating stove at 40 ºC, pulverized in mill and extracted by maceration with 65% EtOH at room temperature for seven days. The ethanolic extract was filtered and the ethanol was removed. Finally, the extract was retake in water and partitioned using organics solvents with increased polarity: CH2Cl2, AcOEt and n-BuOH. We report the isolation and identification of six constituents of the CH2Cl2 fraction: the triterpenes a-amyrin, b-amyrin and lupeol and the steroids b- sitosterol, stigmasterol and spinasterol. The flavanone eriodictyoI was isolated from the AcOEt fraction. The constituents were identified through spectral data of the infra-red, GC-MS, 1H-NMR, 13C-NMR and DEPT. No deaths and other signs of toxicity and adverse effect were observed in the evaluation of acute toxicity with doses up to 5.000 mg/kg, that is the maximum dose for acute oral toxicity test for extract of plants. Also, through DPPH method, AcOEt and n-BuOH fractions of the plant showed good antioxidant activity with IC50 22.52 and 17.44 mg/mL, respectively.